1989
DOI: 10.1007/bf00003873
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate agonists from marine algae

Abstract: The occurrence of three glutamate agonists -glutamic acid, D-homocysteic acid and kainic acid -in a spontaneous mutant of Palmaria palmata is reported. Glutamic acid and D-homocysteic acid, but not kainic acid, were found in the wild-type plant. The closely related glutamate agonist, domoic acid, was found in the red alga Chondria baileyana and in the diatom Nitzschia pungens forma multiseries. In the diatom, domoic acid can build up to high levels in excess of 3 % (dry wt.), making N. pungens a potential comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…This suggests that the effect was primarily upon the diatom and not upon the bacteria. The fact that proline and glutamic acid had approximately the same effects is not surprising as metabolically the two are readily interconvertible; Laycock et al (1989) showed that glutamic acid was present in substantially higher concentrations than proline in domoic acid producing Nitzschia pungens (presumably a strain of P. multiseries) cells grown in non-axenic cultures. Thus, it is probable that the flnal effect resulting from the addition of either amino acid could be attributable more to glutamic acid than to proline.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the effect was primarily upon the diatom and not upon the bacteria. The fact that proline and glutamic acid had approximately the same effects is not surprising as metabolically the two are readily interconvertible; Laycock et al (1989) showed that glutamic acid was present in substantially higher concentrations than proline in domoic acid producing Nitzschia pungens (presumably a strain of P. multiseries) cells grown in non-axenic cultures. Thus, it is probable that the flnal effect resulting from the addition of either amino acid could be attributable more to glutamic acid than to proline.…”
Section: Resultsmentioning
confidence: 99%
“…multiseries, is also a potential source of the glutamate agonist, domoic acid (Laycock et al, 1989). Domoic acid is structurally similar to glutamic and aspartic acid and acts as a potent excitant (agonist) of glutamate receptors; as such it could be an important tool in the study of neurodegenerative disease and N. pungens has been shown to contain >1% of dry wt of domoic acid in culture and could therefore be an excellent source of this compound.…”
Section: Toxins and Pharmacologically Active Compoundsmentioning
confidence: 99%
“…Today, KA is used as a standard reagent in neurobiological research. KA has also been isolated from other species of red algae, such as Alsidium helminthochorton (Calaf et al 1989), Caloglossa leprieurii (Pei-Gen and Shan-Lin 1986), Centroceras clavulatum (Impellizezeri et al 1975), and certain strains of Palmaria palmata (Laycook et al 1989).…”
Section: Introductionmentioning
confidence: 99%